Metabolic response during sport rock climbing and the effects of active versus passive recovery - Watts, P. B.; Daggett, M.; Gallagher, P.; Wilkins, B. (International Journal of Sports Medicine, 2000)
The objectives of this study were to 1) continuously assess oxygen uptake during and after difficult sport rock climbing and 2) to evaluate the effects of active versus passive recovery on post-climbing blood lactate and hand grip strength. Fifteen expert rock climbers attempted to climb (i.e., red point lead) a 20m difficult route (5.12b, YDS scale) set on an indoor climbing wall. Subjects were assigned to either active recovery (AR; n = 8), consisting of recumbent cycling at 25 Watts, or passive recovery (PR; n = 7). Expired air was analyzed during climbing and through a 10-minute recovery period by a lightweight battery-powered open circuit system. Oxygen uptake (VO2) and heart rate (HR) were measured continuously and averaged over 20-second intervals. These data were expressed as averages over the entire climb (VOavg and HRavg) and as peak values. An estimated resting VO2 of 250 ml × min-1 was subtracted from the intervalVO2 values to provide net VO2 data which were subsequently converted to absoluteVO2 values in liters for climbing (C - O2net) and recovery (R - O2net). Total netVO2 was calculated as the sum of C - O2net plus RO2net. Blood samples were obtained via fingerprick at pre-climb and at 1-, 10-, 20-, and 30-minutes post-climb and analyzed for whole blood lactate. Handgrip strength was measured via dynamometry at pre-climb and at 1-, 10-, 20-, and 30-minutes post-climb. Mean climbing time was 2.57 ± 0.41 min. During climbing, VO2avg and HRavg means were 1660 ± 340 ml × min-1 and 148 ± 16 b × min-1 respectively with mean peaks of 2147 ± 413 ml × min-1 and 162 ± 17 b × min-1. Relative VO2avg was 24.7 ± 4.3 ml × kg-1 × min-1 with a mean peak value of 31.9 ± 5.3 ml × kg-1 × min-1. Mean values for C - O2net and R - O2net were 4.009 ± 0.929 L and 2.809 ± 0.518 L respectively for the PR group with mean total net O2 at 6.818 ± 1.291 L. For the AR group mean values for C - O2net and R - O2net were 4.216 ± 1.174 L and 7.691 ± 3.154 L respectively with a mean total net VO2 of 11.906 ± 4.172 L. There was no difference between the groups for C - O2- net, however R - O2net and total netVO2 were significantly different (p < 0.05) between PR and AR. Blood lactate increased significantly with climbing in both AR and PR groups. Lactate remained elevated in the PR group until 30 minutes post-climb, but had returned to pre-climb level by 20 minutes in the AR group. Handgrip strength was significantly decreased at 1-minute post-climb for the AR group, but was not significantly changed for the PR group. Although climbers may be able to attain a plateau in VO2, the observed accumulation of lactate in the blood combined with the elevated recovery VO2 indicate a higher overall energy demand than indicated via the recorded VO2 during climbing. Low intensity active recovery appears to significantly reduce accumulated blood lactate within 20 minutes following difficult climbing, however further research is required to establish whether this strategy is advantageous for subsequent climbing performance.